Status of rheumatic heart disease in rural Pakistan. Issue 4 (12th March 2004) - Rizvi, S F; Khan, M A; Kundi, A; Marsh, D R; Samad, A; Pasha, O
Abstract : Objectives: To determine the community based prevalence of rheumatic heart disease (RHD) in the rural population of the district of Rahim Yaar Khan in Pakistan. Subjects and methods: A representative sample of the rural population of Rahim Yaar Khan district was selected. RHD was screened for by physical examination and the diagnosis was confirmed with echocardiographic Doppler studies. Sociodemographic data on each screened person were collected. Results: 54 cases of RHD were found among the 9430 people screened (prevalence of 5.7 in 1000, 95% confidence interval 4.2 to 7.2). Females were significantly more likely to be affected. There was no significant relation with other factors studied (education, crowding, and socioeconomic status). Less than 20% of those found to have RHD were aware of their diagnosis before participation in this study and only three affected people (8%) were taking rheumatic prophylaxis. Conclusions: There is a high prevalence of RHD among the rural population of Pakistan. The prevalence has not declined over the past three decades. Nearly all people with RHD, including most of those who know their diagnosis, do not receive the benefit of potentially life saving secondary prevention measures.